Effect of Self-efficacy and Social Support Enhancement Program on Hypertension Preventives among Persons at Risk Hypertension in Kantharalak District, Sisaket Province - Kittiyawan, Jariya; Sae-tia, Yuphawadee (Journal of The Royal Thai Army Nurses, 2023)
This quasi-experimental research with a two-group pretest- posttest design. The research objectives were to study an effect of self-efficacy and social support enhancement program on hypertension preventives among persons at risk hypertension. The sample living in the area of responsibility of Don-Ow Sub-district Health Promoting Hospital. The sample consisted of 60 people, divided into the experimental group of 30 people and the control group of 30 people. The instrument used in study was the Self-efficacy with social support enhancement program. Data were collection by using the prevention of hypertension behaviors questionnaire. The content validity was .88 and the reliability was .87.The personal data were analyzed by descriptive statistics, independent t-test.The results showed that the experimental group’s mean scores for preventing high blood pressure behaviors were significantly higher than the control group (p < .05) and mean blood pressure level was at a different control level. statistically significantly different from the control group (p < .05). Suggestions: Sub-district Health Promoting Hospital should apply the Self-efficacy with social support enhancement program in persons at risk hypertension lead to continuous and sustainable behavioral change